LEARNING FROM THE PAST: ASSESSING SUSTAINABILITY STRATEGIES OF THE HERITAGE BUILDINGS THROUGH LEED RATING SYSTEM: (CASE STUDY OF GHADAMES CITY) - SALWA SALEM ALBARSSI; HANAN MANSOUR FARKASH (Scientific Journal of University of Benghazi, 2026)
In the recent dialogues of the sustainable buildings, the relation between heritage architecture and future development has taken an important standing. This because the techniques of traditional buildings have resisted all life and environmental conditions for thousands of years, where human’s comfort and needs are Satisfactorily met through full response to natural resources and climatic conditions and still. However, various passive design strategies and features are not intelligibly incorporated into latest environmental designs and construction solutions. This can be ascribable to the unawareness of their ability to resist current conditions or those unconformity with future sustainability requirements. This study tries to advance the sustainability strategies of heritage buildings and encourage their utilization in the future development. The old city of Ghadames (OCG) will be involved as a study case to determine the extent heritage building features met satisfactorily to the current available sustainability rating systems. Many guidance have been emerged to achieve higher standards of sustainability in new buildings as well as measuring the environmental performance of the projects that involve historical places. In terms of achieving the paper aims, the researcher will use the Leadership in energy and environmental design (LEED) as a guidance of green building design to promote a framework for assessing the sustainability criteria of Ghadames city. LEED tools deal with sustainability of the sites, water efficiency, energy saving, materials and waste management, indoor environmental quality. The researcher will also consult relevant literatures in the field. The study concluded that Ghadames city is an outstanding example of an environmentally engineered desert city, and its sustainable techniques not only performed well against previous conditions but also can be used in both current and future sustainable development.